The integrated educational course as theoretical and methodological foundation of the specialist’s formation both personally of the creative personality in the sistem of the higer technical education - Лузік, Е.В. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2012)
The theoretical and methodological foundations of the integrated courses are considered. The integrated courses are considered as the integral process of the specialist’s formation both personally and professionally which provides the conditions for the further development of the creative personality and preserves his/her creative essence – the tendency to search and transform.